PELATIHAN BAHASA INGGRIS DENGAN TEKNIK SCAFFOLDING UNTUK PEMBELAJARAN DARING BAGI SISWA SMP MUHAMMADIYAH SERPONG - Darmawati Darmawati; Nur Najiba Sukmawati; Pari Purnaningsih; Resti Isnaeni; Sulasih Sulasih (JAMAIKA: JURNAL ABDI MASYARAKAT, 2022)
Muhammadiyah Serpong Junior High School hopes that students can learn to be independent because there is very limited time for teachers to explain in depth each subject, especially during the pandemic, learning is done online. Our Community Service (PKM) will provide English language training to students using scaffolding techniques for online learning. Scaffolding techniques are not new, but we make innovations in the preparation in presentation of materials, it will be very appropriate to the current situation which requires students to learn online. We took the material from the English textbook for junior high school grade 9, then we designed the presentation of the lesson with a scaffolding technique, starting by giving an assessment to determine the level of students' abilities, then compiling exercises containing questions that were in accordance with the students' basic abilities, after that We make instructions that are clear and easy to understand, escorting students to do exercises starting from writing, speaking, understanding then recording their voices in study groups, and conducting self-assessments and providing motivation and encouragement. Provide support and appreciation for each student's achievement. And releasing students to work on assignments independently if they are considered capable.Keywords: scaffolding, online, English training